2016
DOI: 10.11648/j.ajasr.20160206.12
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Dissemination of Some Heavy Metals in Soil Adjacent to <i>Bhaluka</i> Industrial Area, Mymensingh, Bangladesh

Abstract: Heavy metals released from industries causes severe environmental pollution in developing countries. This study has been conducted to evaluate the intensity of heavy metals pollution in soil at 0, 30 and 60 m distances from waste carrying canal of Bhaluka industrial area of Mymensingh, Bangladesh. Lead (Pb), chromium (Cr), copper (Cu), zinc (Zn), iron (Fe) and manganese (Mn) concentrations in soils decreased gradually with the increase of distance from waste canal. Maximum concentration was found at 60 to 0 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
(38 reference statements)
2
8
1
Order By: Relevance
“…In this experiment, the pangas muscle contained a significant amount of Ni rather than other fish tissue; this statement partially supported by Mwakalapa et al (2019). Ali and Khan (2018) Zabir et al, 2016, Rajeshkumar and Li, 2018. Studies on heavy metals accumulation in fish farms pointed the source of contamination could be from sharing one-way waste discharge system of every pond in the farm area, a habitat of the farm, farm ecosystem condition, water quality issues of the farm system, excessive use of growth supplements as feed additives (Ali and Amaal, 2005;Li et al, 2010;Nofal et al, 2019).…”
Section: Concentration Of Heavy Metals In Pangas Organssupporting
confidence: 55%
See 3 more Smart Citations
“…In this experiment, the pangas muscle contained a significant amount of Ni rather than other fish tissue; this statement partially supported by Mwakalapa et al (2019). Ali and Khan (2018) Zabir et al, 2016, Rajeshkumar and Li, 2018. Studies on heavy metals accumulation in fish farms pointed the source of contamination could be from sharing one-way waste discharge system of every pond in the farm area, a habitat of the farm, farm ecosystem condition, water quality issues of the farm system, excessive use of growth supplements as feed additives (Ali and Amaal, 2005;Li et al, 2010;Nofal et al, 2019).…”
Section: Concentration Of Heavy Metals In Pangas Organssupporting
confidence: 55%
“…Unfortunately, in a couple of years, rapidly growing industrialization immensely influence the environmental pollution of the area where all the factories discharge their untreated effluents directly into the canals and then the dumping spread over agricultural lands. Furthermore, several studies reported on heavy contamination of metals (As, Zn, Cr, Cd, Pb, Sr, Ni, Li, Ag, Hg, Co, and Se) in the dumping grounds of almost 300 different industries distributed in Mymensingh district where every day a significant amount of textile dyes, plastics, metal fabricates, diesel, leather tanners are being discharged into the local agricultural areas (Islam et al, 2015;Ahmed et al, 2012;Al Zabir et al, 2016). However, metal contamination of marketed or farmed fish and their diets of Mymensingh has already been examined (Hossain et al, 2016;Al Zabir et al, 2016;Akter et al, 2020), but no systematic comparison of metal contents in pangas and their feeds with the seasonal variation reported yet.…”
Section: Geological Features Of This District Have a Remarkable Blessmentioning
confidence: 99%
See 2 more Smart Citations
“…However, farms of Trishal contain the highest concentrations of Cd, Ni, Cu, and Cr in which the highest load of Pb observed in one farm of Bhaluka. The rapidly growing industrialization of Bhaluka region indicates an alarming scenario of the polluted environment described by Al Zabir et al (2016). Pb, Cu, Cr, and Cd contributed to this extreme situation in Bhaluka as well total Mymensingh district where industrial effluents or anthropogenic origins act as the primary source (Al Zabir et al, 2016;Hossain et al, 2015).…”
Section: Metal Distribution In Pangas Of Mymensingh Region By Pca Andmentioning
confidence: 99%